Spiritual physicke to cure the diseases of the soule, arising from superfluitie of choller, prescribed out of Gods word. Wherein the chollericke man may see the dangerousnesse of this disease of the soule vniust anger, the preseruatiues to keepe him from the infection thereof, and also fit medicines to restore him to health beeing alreadie subiect to this raging passion. Profitable for all to vse, seeing all are patients in this disease of impatiencie. [electronic resource] : (1600)
Summary goes here